Antimicrobial spectrum activity of lauric acid & chitosan - Salleh, Eraricar (Faculty of Chemical and Natural Resource Engineering, 2009)
Future work will focus on the use of biologically active derived antimicrobial compounds bound to biopolymers. However many natural antimicrobials have a limited spectrum of activity and are effective only at very high concentrations. The need for new antimicrobials with wide spectrum activity and low toxicity is increasing. The objectives of this research include to study the behaviour of lauric acid (LA) and chitosan as an antimicrobial agent, to determine the antimicrobial effects of LA and chitosan against food spoilage microorganisms and to investigate the inhibition growth of combined antimicrobial agent on food spoilage microorganisms. The antimicrobial activity testing was based on the agar diffusion method and liquid culture test based on standard serial broth dilution assay. The present test emphasizes on the efficacy of chitosan and LA to inhibit the growth of selected Gram-positive food pathogenic bacteria i.e. Bacillus subtilis and Gramnegative food pathogenic bacteria i.e. Escherichia coli. The result shows that chitosan and LA have good inhibitory effects against E. coli and B. subtilis respectively. It is also suggested that the combination of chitosan and LA is insufficient to retard the growth of Gram-negative bacteria, E. coli. However, it shows a good inhibition effect on Gram-positive bacteria, B. subtilis as can be seen on the area of zone inhibition in agar diffusion method. The liquid culture test shows that chitosan is not effective in inhibiting the microbial growth in an aqueous condition compared to agar plate test. In contrast, lauric acid gave a better inhibition effect in liquid culture test. Combination of chitosan and LA showed obvious effects towards inhibition of B. subtilis and E. coli indicated that they had synergistic antimicrobial effect in solid or liquid condition.